Soil stabilization using rice husk ash and cement for pavement subgrade materials - Eksana Wibowo, Dian; Agung Ramadhan, Dymas; Endaryanta; Prayuda, Hakas (Revista de la Construcción. Journal of Construction, 2023)
This study employs rice husk ash and pozzolan cement as additional soil stabilization materials. This study aims to evaluate the bearing capacity of the soil to be used as embankment soil for subgrade pavement materials. The soil samples were collected from two different areas in the Yogyakarta region, Indonesia, namely the Wates and Imogiri regions. This study consists of experimental approach that defines a soil embankment for road subgrade with a trapezoid-shaped with top dimension of 10 cm x 20 cm, a base dimension of (20 cm x 40 cm), and a height of 10 cm. In addition, the specimens in this study were divided into two groups: the embankment with a 1 cm-thick sand base and the embankment without a sand base. The USCS classified the samples from Wates as OH-type or organic clays with moderate to high plasticity and by AASTHO as group of A-7-5 (22). The soil from Imogiri was categorized as inorganic silt or fine diatoms sand with OH clumps or AASTHO classified this soil as group A-7-5 (11). The addition of rice husk ash and pozzolan cement as stabilizing soil materials has a moderate effect on the engineering properties of the soil, particularly the bearing capacity and bearing capacity ratio of soil. This soil stabilization also demonstrates that the engineering properties of the stabilized soil significantly improved compared to the original soil without stabilization.